The Effect of Cognitive Behavioral Group Counseling on Bullying and Empathy Levels of Adolescents - Ime, Yakup (Anales de Psicología / Annals of Psychology, 2024)
Bullying can have negative effects on the physical and mental health of adolescents. Adolescents who are victims of bullies may show various signs of problems. The present study examines the effect of a cognitive-behavioral group counseling program on bullying tendencies and empathy skills among adolescents. Experimental and control groups were formed in the study, and 35 adolescents were randomly assigned to the experimental (18) and control (17) groups. Bullying Scale and Adolescent KA-SI Empathic Tendency Scale were used as data collection tools. Cognitive behavioral group program consisting of 10 sessions was applied to the experimental group, and no intervention was made to the control group. After the end of the intervention program, post-test was applied to both groups. Two months later, follow-up measurements were applied to both groups. After the intervention, the bullying tendencies of the adolescents in the experimental group decreased and their empathy skills improved. Thus, the effectiveness of the created program in reducing bullying and developing empathy skills in adolescents was confirmed. The present study shows that a cognitive-behavioral group counseling program can reduce bullying behaviors and improve empathy skills in adolescents.